Penerapan Nilai-nilai Berkelanjutan dalam Pendidikan Perubahan Iklim: Sebuah Kajian Epistemologi dan Aksiologi - Puspa Nuwangi, Pohaci; Nahadi; Anwar, Sjaeful; Riandi (Universitas Insan Budi Utomo, 2023)
This research aims to examine the integration of education for sustainable development (ESD) values in climate change education (CCE) (CCESD) from an epistemological perspective, namely focusing on history and the development of those knowledges; and an axiological perspective, namely the values that build it. The research was carried out qualitatively using a literature study method, where all documents used as data sources were reading material that discussed